Cloud-Based Collaborative Media Service Framework for HealthCare. (31st March 2014) - Hossain, M. Shamim; Muhammad, Ghulam
With the increasing growth of media cloud technologies, web service technologies, and smartphones equipped sensors, a number of collaborative media services are being built for ubiquitous user access. Currently, collaborative services are being used in several areas like healthcare, defense, education, and so forth. However, due to the challenge of providing such service to users in terms of computations, communications, processing, and storage, there is a growing need for an infrastructure to have on-demand access to a shared pool of configurable computing resources (e.g., networks, storages, servers, applications, and services). Cloud computing is such a paradigm or infrastructure to provide configurable platform to support the collaborative service. In this paper, we present the corresponding framework of collaborative media service for efficient collaboration between caregivers and healthcare professionals. The experimental results not only showed our solution is more efficient than the similar system but also proved that our solution can work well for web service-based collaborative environment.